Bifunctional water-electrolysis-catalysts meeting band-diagram analysis: case study of "FeP" electrodes. Issue 38 (24th September 2020) - Ali, Rashad; Shan, Aixian; Saranya, Govidarajan; Jian, Xian; Mahmood, Asif; Mahmood, Nasir; Chen, Mingyang; Yang, Yunguo; Lau, Woon-Ming
Abstract : Band-diagram-based perspective and guidance for designing and screening high-performance bifunctional catalysts for water-electrolysis are developed based on the case study of "FeP" electrodes. Abstract : Bifunctional catalysts for water-electrolysis are developed to simplify electrode- and cell-manufacturing. Hitherto, screening bifunction catalysts relies on experimental trials of high-performance cells and theoretical calculations of free-energy changes in the HER/OER intermediate steps, with high costs and constraints. Herein, we derive from the inevitable electrode-surface oxidation in water electrolysis and the semiconductor physics of such an oxidized electrode surface a band-diagram perspective: the oxidized electrode surface governing the catalytic activities in a bifunctional water-electrolysis cell should be a semiconductor with an effective bandgap not much larger than the HER-OER electrochemical potential gap of 1.23 eV. This perspective and its applications are elaborated with a set of experimental and DFT-computational results with FeP as a nominal bifunctional catalyst on nickel electrodes for the construction of a high-performance cell exhibiting 10 mA cm −2 at 1.40 V. The proposed "bandgap screening" is easy, low-cost, and applicable for expediting the development of new bifunctional catalysts.